Integrating Empathetic and Normative Approaches in Hadith Interpretation: A Contextual Study of Prophetic Ethical Communication in Da'wah - Mauludin, Hilman; Khadijah, Ifah (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
This article explores an integrative methodological approach to hadith interpretation by combining normative and empathetic perspectives in the context of prophetic communication. Using a qualitative-explorative design and thematic-contextual analysis, this study examines selected hadiths that reflect both legal norms and compassionate responses from the Prophet Muhammad (PBUH) during da'wah encounters. Key examples include the hadiths of the Bedouin urinating in the mosque, the young man seeking permission to commit fornication, and the female adulterer requesting punishment. These cases demonstrate how the Prophet upheld Islamic law while also applying emotional intelligence and situational awareness. The findings suggest that empathy does not negate legal norms but enhances the effectiveness of da'wah through moral education and audience-sensitive communication. This integrative approach aligns with the ethical foundations of maqāṣid al-sharī‘ah and the prophetic value of raḥmah. In contemporary plural societies, such an approach provides a more effective and humane strategy for Islamic propagation. The study calls for Islamic scholars, preachers, and educators to adopt ethical-contextual hadith interpretation in both academic and da'wah settings